United Nations Convention on the Law of the Sea - Proelß, Alexander; Maggio, Amber Rose; Blitza, Eike; Daum, Oliver (Verlag C.H.BECK Recht - Wirtschaft - Steuern, 2021)
The United Nations Convention on the Law of the Sea (UNCLOS) entered into force in 1994. Meanwhile, it has been ratified by about 160 states, including all the Member states of the EU and the EU itself. The Convention defines the rights and duties of states with regard to the use of the seas. UNCLOS consolidates customary international law and various conventions previously adopted by the international community. This Treaty, the most comprehensive ever concluded, is often referred to as ‘the constitution for the seas’. The commentary employs a systematic methodology whereby each provision is examined and analysed element by element. The issue of the suitability of the Convention to deal with the challenges facing the modern law of the sea, such as the exploration and exploitation of non-mineral resources or the protection of the marine environment in general, occupies a central editorial focus of this work. The commentary deals with all the provisions of the Convention article-by-article. Alexander Proelss is Professor of Public International Law at the University of Trier, specialising in the law of the sea. The authors are renowned experts on the law of the sea from all over he world.